Impact of immunosuppression on the incidence of early subclinical renal allograft rejection: implications for protocol biopsy policy. - Roberts, I; Stratopoulos, C; Zilvetti, M; Reddy, S; Friend, P (2009)
In order to determine the impact of immunosuppression (IS) on the incidence of early subclinical rejection (SCR), we studied two groups of patients receiving different immunosuppressive regimens. Patients received cyclosporin (CsA), azathioprine and prednisolone (group 1; n = 304) or IS according to immunological risk (group 2; n = 150). The highest-risk patients received basiliximab induction, tacrolimus, mycophenolate mofetil (MMF) and prednisolone; medium-risk patients CsA, MMF and prednisolone; low-risk CsA, azathioprine and prednisolone. Protocol biopsies were performed in all patients, irrespective of graft function, on days 7 and 28 post-transplantation. Only patients with good stable function at the time of biopsy were included for assessment of SCR. Group 2 patients showed significant reductions in total rejection frequency (32.6% vs. 57.2%, P = <0.0001) and SCR frequency in day 7 protocol biopsies (2% vs. 13%, P = <0.05). In group 2 patients, all SCRs, but not borderline changes, were treated. Untreated borderline changes did not have an adverse impact on graft function at 1 year post-transplantation. New immunosuppressive regimens may reduce subclinical in addition to clinical rejection-frequency, suggesting that the relative benefit of early protocol biopsies in detecting SCR is also reduced.